Síntese e caracterização de biofilmes à base alginato de sódio reticulado com poliacrilamida catiônica - ABREU JÚNIOR, Aquiles Ferreira de (2017)
Biofilms based on sodium alginate (AS) crosslinked with cationic polyacrylamide (PAMc) of high molar mass were made by the casting technique. In this study, the central rotational compound design (DCCR) was used and 11 trials were performed. The biofilms produced were characterized with respect to moisture (ω), water solubility (S), water vapor permeability (PVA), thickness (σ), absorption spectroscopy in the infrared region with Fourier transform (FTIR), microscopy scanning (SEM) and mechanical properties. The experimental results showed that biofilms with lower glycerol contents obtained lower moisture content. It was observed that for the solubility and permeability to water vapor, the lower values observed were influenced by the concentrations of PAMc. Assay 5 (AS 6.0g, GLI 1.0g, PAMc 2.5%) presented lower values of ω and PVA, with possible application as food coatings and assay 10 (AS 6.0g, GLI 3.0g; PAMc 2.5%) higher S, and can be applied in biodegradable packages. The results obtained through FTIR confirmed the chemical interaction between AS and PAMc. Morphological analyzes showed that biofilms showed heterogeneity when the concentrations of MAP were increased. Regarding the mechanical properties, tensile strength (TR) and Young's modulus (E) were found to increase when the PAMc concentrations were higher and the deformation decreased when glycerol concentrations were high. Trial 11 (AS 6.0g, GLI 3.0g, PAMc 2.5%) showed higher TR (14.06 MPa) and E (21.17 MPa), with potential for applications as biodegradable bags.